The Notary Protocol File Managerial - Theodorus Kevin Purinsyah Putra; Nany Pudjianti Suwigjo (Universitas Islam Sultan Agung, 2023)
The Regional Supervisory Council (MPD) of Semarang Regency acts as a supervisor for the performance of all Notary Offices in Semarang Regency in implementing the spearhead of the Notary Supervisory Council (MPN). The managerial implementation of Notary protocol files in Semarang Regency in Act No. 30 of 2004 on Notary Positions is not regulated in detail so that in its implementation it is left to the policies of each Notary Office. This study aims to determine and analyze the managerial implementation of Notary protocol files at the Semarang Regency Notary Office and the implementation of managerial supervision of Notary protocol files by the Semarang Regency MPD. The research method used in this research is empirical juridical using primary and secondary data. The results of this study indicate that the managerial implementation of the Notary protocol file is carried out based on Articles 8, 12 and 15 paragraph (1) of Act No. 30 of 2004. Supervision from the MPD of Semarang Regency is carried out 2 times a year and has carried out digitization of protocol files through Link and SILANDU.